The Analysis of Student’s Digital Literacy with Microsoft E-Learning Media - Fige Arief Kusumo; Bambang Subali; Sunarto Sunarto (Universitas Negeri Semarang, 2022)
Digital literacy is important to deal with digital disruption wisely. The ease of accessing the internet makes digital literacy an important thing. digital literacy can prevent the bad condition in digital era. The students can prevent all bad sector of digital world like hoax, cyberbullying, cybercrime, violence, and the others. This study aims to determine the level of digital literacy students during the implementation of Microsoft e-learning media that is used for learning in elementary schools, especially in fifth grader. The population is the elementary students of SD Ihsaniyah 1 Tegal. This study used a simple random sampling and data collection was in the form questionnaire, which was distributed to students. There are 30 respondens for sampling. This research uses descriptive quantitative research using survey method research to determine the level of digital literacy of students. The results show that the digital literacy of students while using Microsoft-based e-learning products is in the medium category with an average of 75.2%. So, the strengthening of digital literacy in learning is also strengthened through creative and innovative digital learning media. Through the analysis, students have the potential to access the digital because digital literacy skills are at the medium stage.